(3cfR GdeYGfi aj TQM MQR GdCeGfi hhLg GdJgGfis - (3CHh ESMGb EHQGgje Hf YeQ Hf EHQGgje Hf Ndjd GdLYHQis; (3GdTGWHj GdebQF GdVQjQ , CHh eMeO,J (B590 (3g` s
(3ChdgG (B:s
(3GdMeO eHOF GdCee , hefTF GdQee , GdPi Yde HGdbde hHYO aEf aVjdI GdYde HjfI hCLd GdYdhe Yde cJGH QH GdYGdejf hdeG Cgdfi Gddg ddEbQGA HMQe NdjdI EHQGgje hMHhJ GdWdHI ef ENhGfi HcJGH cfR GdeYGfi s
(3BNQgG (B:s
(3GdEOZGe GdcHjQ CMO hNeShf ehVhYkG (B: (3GdcJH HGdMb , hRjf ddfGS ShQI GdfSGA , hUdi Gddg GfJgi s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV YHGQGJgG HGdMeQIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B110s
Keywords: (3GdbQGAGJ hGdJLhjOs